2013
DOI: 10.1088/0967-3334/34/3/n15
|View full text |Cite
|
Sign up to set email alerts
|

Waveform analysis of tremor may help to differentiate Parkinson's disease from drug-induced parkinsonism

Abstract: In this study, we analyzed the waveform characteristics of resting tremor by accelerometer recordings in patients with drug-induced parkinsonism (DIP) and Parkinson's disease (PD). We prospectively recruited 12 patients with tremulous PD and 12 patients with DIP presenting with resting tremor. Tremor was recorded from the more affected side and was recorded twice for a 60 s period in each patient. Peak frequency, amplitude and all harmonic peaks were obtained, and the asymmetry of the decay of the autocorrelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Majchrzak et al demonstrated that, compared to healthy controls, the harmonic index of tremor motions (the distance of the spectrum to the single narrow peak, which was normalized to the highest peak) was significantly higher in patients with Parkinsonian tremor, essential tremor, and cerebellar tremor ( 24 ). Jang et al reported that the harmonic ratio (the value of the total harmonic peak power divided by the number of harmonic peaks) was remarkably lower in PD patients than in drug-induced Parkinsonism patients ( 25 ). In another study, Muthuraman et al .…”
Section: Discussionmentioning
confidence: 99%
“…Majchrzak et al demonstrated that, compared to healthy controls, the harmonic index of tremor motions (the distance of the spectrum to the single narrow peak, which was normalized to the highest peak) was significantly higher in patients with Parkinsonian tremor, essential tremor, and cerebellar tremor ( 24 ). Jang et al reported that the harmonic ratio (the value of the total harmonic peak power divided by the number of harmonic peaks) was remarkably lower in PD patients than in drug-induced Parkinsonism patients ( 25 ). In another study, Muthuraman et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although walking and tremor motions are identified as major influencing artifacts, they can be mainly eliminated by using averaging algorithms, owing to their symmetric waveforms. A deep analysis made by Jang et al [25] reported that tremors in PD are symmetric. In the same vein, human gait has been illustrated to have a sinusoidal form, even at high walking speeds [26].…”
Section: Methodsmentioning
confidence: 99%
“…This provides the clinician at zero cost (provided they have a telephone) with an instant alternative to electromyographic tremor studies. Spectral analysis of accelerometer (Hossen et al, 2013 ) and gyroscopic (Bhidayasiri et al, 2014 ) measurements can discriminate between PD tremor and Essential Tremor (ET) or between idiopathic and drug-induced parkinsonism (Jang et al, 2013 ). Accelerometer studies have even attempted to subdivide these conditions, for example separating patients with essential tremor into those that are position-dependent vs. position-independent (Golan et al, 2004 ), or differentiating tremor frequency characteristics of PD patients under resting vs. stressed states (Lee et al, 2016 ).…”
Section: Technologiesmentioning
confidence: 99%